OP78 Are quality of life and family expenditure on physical activity associated with physical activity in 2–4-year-old children?. (September 2018) - Tinner, L; Kipping, R; White, J; Jago, R; Metcalfe, C; Hollingworth, W
Abstract : Background: Despite the well-described health benefits associated with physical activity, many children do not engage in the recommended level of physical activity. To inform public health interventions, there is a need to determine factors associated with physical activity in children. We examined the extent to which the Pediatric Quality of Life Inventory (PedsQL) and family expenditure on physical activity were associated with minutes spent physically active and in moderate-to-vigorous physical activity (MVPA) per day in young children. Methods: Cross-sectional study with a sample of 81 children aged 2–4 years in the South West of England, taking part in the Nutrition and Physical Activity Self-Assessment for Child Care (NAPSACC UK) feasibility randomized controlled trial. We ran descriptive statistics, along with Student t-tests to determine differences by gender, age and parental education and compare physical activity on nursery and non-nursery days. The associations between physical activity, PedsQL scores (physical and psychosocial) and family expenditure on physical activity were assessed using mixed effects linear regression models in Stata 14.2. Results: 88.89% of children did not meet the recommended 180 min daily physical activity. Children spent a mean (SD) of 141.90 (33.10) minutes per day being physically active with 22.21 min per day (SD=9.87) in MVPA. Children spent more minutes being active on nursery days than non-nursery days (146.89 vs 137.22, p=0.05). Boys were more physically active than girls, spending 148.95 vs 133.93 min in daily activity (p=0.04). Older children were more physically active than younger children (p=0.01). There were no differences in physical activity by parental education. Approximately half (50.62%) of the sample spent less than £9.00 weekly on their 2–4-year-old's physical activity. Children scoring in the highest third of PedsQL physical functioning scores had higher levels of MVPA (4.06 95% CI −0.41 to 8.54, p-value 0.07). There was no evidence of a beneficial association between positive PedsQL psychosocial scores, or higher parental expenditure on physical activity, with more minutes spent being active or in MVPA. Conclusion: Physical activity was below the recommended 180 min of daily physical activity for this age group. Children were more physically active on nursery days. There is weak evidence of an association between better PedsQL physical scores and higher levels of MVPA. More time spent being physically active and in MVPA was not associated with higher expenditure on physical activity in this age group, but further examination in larger datasets is needed.